Effectiveness of direct-acting antivirals in maintenance hemodialysis patients complicated with chronic hepatitis C. Issue 48 (25th November 2020) - Li, Chunhong; Liang, Jing; Xiang, Huiling; Chen, Haiyan; Tian, Jie
Abstract : Abstract: Hepatitis C virus (HCV) infection is very common in maintenance hemodialysis patients, causing high morbidity and mortality. This study aimed to evaluate the effectiveness and adverse events of direct-acting antivirals (DAAs) in maintenance hemodialysis patients complicated with chronic hepatitis C in real-world clinical practice. In this retrospective observational study, hemodialysis patients with chronic hepatitis C infection in the Third Central Hospital of Tianjin outpatient were screened, and appropriate treatment plans were selected accordingly. Totally 25 patients diagnosed with chronic hepatitis C and treated with DAAs for 12 weeks or 24 weeks were included. The sustained virologic response (SVR) rate obtained 12 weeks post-treatment (SVR12) was evaluated. Laboratory indexes and adverse reactions during the treatment process were also assessed. A total of 25 cases met the eligibility criteria and provided informed consent. Except for 1 patient who discontinued the treatment due to gastrointestinal bleeding, the remaining 24 cases completed the treatment cycle with 100% rapid virologic response (RVR) and 100% SVR12, with no serious adverse reactions recorded. Maintenance hemodialysis patients complicated with chronic hepatitis C in Chinese real-world setting tolerate DAAs very well, with a viral response rate reaching 100%.